The wide-aperture gamma-ray telescope TAIGA-HiSCORE in the Tunka Valley: Design, composition and commissioning - Gress, O.; Astapov, I.; Gress, T.; Epimakhov, S.; Fedoseev, E.; Gafarov, A.; Gorbunov, N.; Grebenyuk, V.; Grinuk, A.; Grishin, O.; Horns, D.; Ivanova, A.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2017)
The new TAIGA-HiSCORE non-imaging Cherenkov array aims to detect air showers induced by gamma rays above 30 TeV and to study cosmic rays above 100 TeV. TAIGA-HiSCORE is made of integrating air Cherenkov detector stations with a wide field of view (0.6 sr), placed at a distance of about 100 m. They cover an area of initially ∼0.25 km$^2$ (prototype array), and of ∼5 km$^2$ at the final phase of the experiment. Each station includes 4 PMTs with 20 or 25 cm diameter, equipped with light guides shaped as Winstone cones. We describe the design, specifications of the read-out, DAQ and control and monitoring systems of the array. The present 28 detector stations of the TAIGA-HiSCORE engineering setup are in operation since September 2015.